2018
DOI: 10.1177/1457496918812208
|View full text |Cite
|
Sign up to set email alerts
|

Lower Risk of Recurrence After Mesh Repair Versus Non-Mesh Sutured Repair in Open Umbilical Hernia Repair: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: Background and Aims: The use of mesh repair in a small- or middle-sized umbilical hernia remains controversial, and evidence is based on only few and small heterogeneous randomized trials. The primary aim was to assess differences, if any, in recurrence (clinical and reoperation), and secondary aim was to assess differences in infections, seroma formation, hematomas, chronic pain, cosmetic result, and quality of life. Method: A systematic review (predefined search strategy) and meta-analyses were conducted bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0
5

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 33 publications
2
32
0
5
Order By: Relevance
“…There was no difference between the groups regarding the risks of SSI, haematoma or chronic pain. These findings are in agreement with other reviews, in which mesh repair was associated with a lower rate of recurrence and an increased rate of seroma compared with suture.…”
Section: Discussionsupporting
confidence: 93%
“…There was no difference between the groups regarding the risks of SSI, haematoma or chronic pain. These findings are in agreement with other reviews, in which mesh repair was associated with a lower rate of recurrence and an increased rate of seroma compared with suture.…”
Section: Discussionsupporting
confidence: 93%
“…All concluded that mesh is superior to sutures in terms of decreasing recurrence. The most recent high-quality meta-analysis 44 included data from RCTs 37,38,46 -48 , retrospective cohort studies 26,49 -51 prospective observational studies 25,31 and studies from hernia registries 40,52,53 . All found that the recurrence rate decreased with the use of mesh compared with sutures, without increasing surgical-site infections, seroma, haematoma or chronic pain.…”
Section: Quality Of Evidence: Strength Of Recommendation: Strongmentioning
confidence: 99%
“…Evidence is limited for hernia defects smaller than 1 cm. A subgroup analysis of a meta-analysis 44 suggested that mesh is also beneficial for small defects, in decreasing recurrence rates. More evidence is needed concerning the role and optimal placement of mesh in patients with an umbilical hernia smaller than 1 cm 44 .…”
Section: Quality Of Evidence: Strength Of Recommendation: Strongmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent RCTs and registry studies have highlighted the effectiveness of laparoscopic mesh repair for inguinal hernia, with similar recurrence rates and risk profiles, but less postoperative pain, quicker recovery and less chronic pain. The benefits of mesh repair in inguinal hernia are replicated in primary ventral (umbilical and epigastric) hernia, with significantly lower recurrence rates compared with non‐mesh repair demonstrated in high‐quality RCTs, national registry studies and meta‐analyses.…”
mentioning
confidence: 99%